2021
DOI: 10.1002/brb3.2384
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping, resilience, and sleep during the COVID‐19 pandemic: A representative survey study of US adults

Abstract: Introduction:The COVID-19 pandemic is a global health emergency resulting in widespread death and substantial disruption to daily life. Previous research has shown that novel disease outbreaks are associated with high stress levels and sleep impairments that lead to neuropsychiatric consequences. Therefore, it is vital to study both stress and protective factors such as coping and resilience that may hinder or help sleep quality during the COVID-19 pandemic. Further, as gender disparities exist in sleep qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 143 publications
(239 reference statements)
0
9
0
1
Order By: Relevance
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“…The type of population was categorized as follow: adolescents (6 studies) [ 71 , 81 , 87 , 92 , 108 , 138 ], children (1 study) [38], general population (66 studies) [ 40 , 42 , 43 , 46 , 48 , 49 ], [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , 59 , 60 , [64] , [65] , [66] ], [ [68] , [69] , [70] , 72 , 73 , 76 , [78] , [79] , [80] ], [ [82] , [83] , [84] , [85] , 88 , 89 , 101 , 103 ], [ 104 , 109 , 110 , 113 , 117 , 120 , 121 ], [ 123 , 128 , 129 , 131 , 134 , 135 , 137 ], [ 139 , [141] , [142] , [143] , [144] , [145] , 147 , [150] , [151] , [152] ], [ 154 <...…”
Section: Resultsmentioning
confidence: 99%
“…Dismantling research should be conducted to examine more precisely whether certain elements of coping strategies and cognitive dispositions are more relevant than others for influencing sleep quality when adjusting to crises. One such variable that may be operating is the element of control [ 6 , 71 , 72 ]. Controlling one’s constructive response to situational stress can be considered a form of proactive resilience-based coping [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigations exploring individuals’ sleep during the COVID-19 pandemic point to patterns of diminished sleep quality as well as collective disruptions to daily life [ 5 ]. Sleep quality is known to be shifted or moderated by stress [ 6 ], but the pandemic presented global changes and concerns beyond typical shifting stress levels. Thus, it is no surprise that studies have demonstrated diminished sleep quality as a result of COVID-19 related stressors and collective issues.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested resilience and coping strategies play an important role in affecting DP ( Chong et al, 2021 ; Di Giuseppe et al, 2021 ; Di Trani et al, 2021 ; Li P. et al, 2021 ; Nituica et al, 2021 ; Perry et al, 2021 ). Studies also showed gender differences in coping strategies and resilience ( Gargiulo et al, 2021 ; Reisch et al, 2021 ; Yan et al, 2021 ; Zhang X. et al, 2021 ), and this could partially explain the gender differences regarding the differential associations between work hours and sleep duration and DP ( Di Giuseppe et al, 2021 ). As the etiology and mechanism of burnout remain elusive, these findings would help understand the pathogenesis of physician burnout.…”
Section: Discussionmentioning
confidence: 99%